Keabsahan Jual Beli Tanah Tanpa Melalui Pejabat Pembuat Akta Tanah di Kota Jayapura - Palenewen, James Yoseph; Tanati, Daniel; Solossa, Marthinus (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The world is developing rapidly due to technological advances. But currently, most people in Jayapura City still carry out land sales transactions without permission from the authorized official, in this case the duties and responsibilities of the Land Deed Making Officer (PPAT). This study aims to determine whether or not land sales are valid without PPAT permission and legal protection for buyers who make land sales without PPAT permission. In this study, normative and empirical juridical are used. This means that it is related to laws, literature, written regulations, and other legal sources that are secondary and real life in the field. The results of this study indicate that if the purchase of land made and witnessed by the village head/sub-district head of Jayapura City has met the material requirements and is not carried out secretly, then the sale and purchase of land is considered valid according to law. However, to provide legal protection for the community in Jayapura City, both sellers and buyers must come to the Village/Sub-district Office to convey the intent and purpose related to the land to be sold and to be purchased. The village head/sub-district head and several members of his staff as witnesses. After land measurement, the data will be recorded in the Village/sub-district book.